2013
DOI: 10.1021/jp401353e
|View full text |Cite
|
Sign up to set email alerts
|

Post-Self-Assembly Cross-Linking to Integrate Molecular Nanofibers with Copolymers in Oscillatory Hydrogels

Abstract: We study the use of post-self-assembly cross-linking to combine molecular nanofibers of hydrogelators with copolymers to generate oscillatory materials using the Belousov-Zhabotinsky reaction. The formation of nanofibers from designed hydrogelators provides multiple polymerizable sites for copolymerizing with N-isopropylacrylamide and for attaching a catalytic ruthenium bipyridine complex on the copolymer. The combination of supramolecular self-assembly with copolymerization offers a versatile and facile appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Recently, our group developed polymer enhanced hybrid self-recovering hydrogels via glucose oxidase mediated polymerization 24. Another post-self-assembly cross-linking approach was reported by Xu et al , who demonstrated that in situ photo-polymerization of acrylic modified oligopeptide hydrogelators with copolymers can achieve a tough hydrogel 25,26. Moreover, these hydrogels have been utilized in multiple applications such as the immobilization of enzymes, controlled release of drugs, controlled cell adhesion and biomimetic materials 2124,2729…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group developed polymer enhanced hybrid self-recovering hydrogels via glucose oxidase mediated polymerization 24. Another post-self-assembly cross-linking approach was reported by Xu et al , who demonstrated that in situ photo-polymerization of acrylic modified oligopeptide hydrogelators with copolymers can achieve a tough hydrogel 25,26. Moreover, these hydrogels have been utilized in multiple applications such as the immobilization of enzymes, controlled release of drugs, controlled cell adhesion and biomimetic materials 2124,2729…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we report herein a dual enzyme-mediated redox initiation to achieve post-self-assembly cross-linking of acrylic modified hydrogelators (NapFFK-acrylic acid, Scheme S1a†)25,26 with monomers for hybrid hydrogel generation. The injectable supramolecular hydrogel is printed into a 3D structure due to the sol–gel transition and quick recovery during the pressure-driven prototyping.…”
Section: Introductionmentioning
confidence: 99%
“…[90, 179182] The simplicity of this approach has result in the subsequent design and development of a large group of self-assembling, peptidic hydrogelators capped by Nap motif. [22, 106, 183185]…”
Section: Supramolecular Hydrogels Made Of the Basic Biological Buimentioning
confidence: 99%
“…One way to overcome this issue is through post-assembly crosslinking, where the cleavage sites are chemically conjugated onto the peptide nanostructures, ensuring surface degradation. [20] However, this method suffers from the complicated procedure of crosslinking chemistry and subsequent removal of the potentially toxic initiators. Another method is to incorporate MMP degradable sequences into the main peptide design such as RADA peptides, [21] multi-domain peptides, [22] and bhairpin peptides [23] to form enzyme-responsive hydrogel systems.…”
Section: Introductionmentioning
confidence: 99%